Bringing Stories to Life: Investigating the Role of Stories in Young EFL Learners’ Reading Comprehension - Triulandari, Aisyah; Setyarini, Sri; Purnawarman, Pupung (Universitas Jambi, Magister Program of English Education Department, 2026)
Young EFL learners, especially in Indonesia, often encounter challenges in reading comprehension due to linguistic limitations and cultural unfamiliarity, which can hinder both understanding and motivation. Although reading comprehension is emphasized in the national curriculum, the need for more effective and contextually relevant instructional strategies remains pressing. This study explores the role of stories in supporting young EFL learners’ reading comprehension. Employing a qualitative approach, data were collected through open-ended questionnaires and semi-structured interviews with 10 primary school English teachers in Indonesia. The findings reveal that each stage of the narrative genre contributes uniquely to reading comprehension. Orientation supports literal understanding through vocabulary exposure and contextual clarity; complication fosters inferential thinking by enabling prediction and causal reasoning; and resolution along with re-orientation promote critical comprehension through reflection on character actions and moral lessons. Additionally, the study, found that teachers implemented various scaffolding strategies, including visual aids, questioning techniques, and pre-reading tasks, to enhance learners' engagement with the text. The study concludes that story-based instruction, when supported by appropriate pedagogical strategies, is highly effective in improving comprehension skills in young EFL learners and should be more widely adopted in early English language education.